Revitalisasi Permukiman Suku Bajo di Desa Kabalutan - Ristianti, Novia Sari (Ruang, 2015)
This study aims to arrangement implementation of buildings and the environment in residential areas Bajo in Kabalutan Village to realize the layout of buildings and neighborhoods and livable, identity themselves, productive and sustainable. Development of the Bajo settlement revitalization must be adapted to the local character of society which has social and cultural life of local governance. Dwelling houses were established in the village Kabalutan a house above the sea level with pillars at the bottom of a shallow sea. The houses surrounding the small islands (with a diameter of 10-20 meters) or elongated follow the access that connects the settlements that surround the small islands. Therefore, control settings and utilization should depart from local character.